Fostering guardians for frontline medical disputes: a government-led medical dispute mediator training program in Taiwan - Wan-Ting Chen; Yu-Ying Huang; Wen-Wen Chen; Yueh-Ping Liu; Chung-Liang Shih; Yi-Chih Shiao; Chih-Chia Wang (BMC, 2022)
Abstract Background Mediation is increasingly used for medical dispute resolution, and the particularity of such mediation necessitates specialized training. In response to the promotion of compulsory mediation ahead of a legislation in Taiwan, we invited experts with an interdisciplinary team to design a case-based mediator training workshop. Our study aimed to investigate the learning outcomes of trainees and analyze their perspectives. Methods We recruited 129 trainees of a non-probability convenience sample who served as mediators or have dealt with medical dispute-related cases to undergo 2.5 h of lectures (introduction; procedure; roles of two mediators; principles and techniques of mediation; dispute arrangement; and issue analysis) and 1.5 h of case-based exercises. An after-class survey was conducted using a 4-point Likert-type scale to evaluate trainees' viewpoints and learning outcomes. A total of 104 questionnaires were collected (response rate: 80.6%). Results The professions of the participants were medical (56%), law (16%), and administration and others (28%). Males considered the course more helpful (3.79 vs. 3.63, p = 0.053) and more important (3.88 vs. 3.74, p = 0.042) than did females. Participants with a legal background scored the highest in helpfulness (3.84), followed by medical (3.74) and administrative (3.63) professionals. Medical and administrative professionals scored the highest (3.85) and lowest (3.76), respectively, on importance. Respondents with more than 10 years (3.81) and less than 1 year (3.79) of experience produced higher scores in helpfulness. Respondents with 1-5 years of experience (3.68) were found to be less likely to agree with the practical importance of course content compared with other groups of trainees. Administrative professionals obtained the highest scores (89.68) in written examinations. Conclusions There are variations in mediators' perspectives based on gender, occupation, and work experience. Our nationwide mediation training workshop can be utilized to cultivate capabilities of mediators for handling medical disputes to achieve the goal of non-litigation in medical disputes.